2007
DOI: 10.1161/hypertensionaha.107.089995
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of 17β-Estradiol on Function and Expression of Estrogen Receptor α, Estrogen Receptor β, and GPR30 in Arteries and Veins of Patients With Atherosclerosis

Abstract: Abstract-Venous complications have been implicated in the adverse effects of hormone replacement therapy. This study investigated acute effects of the natural estrogen, 17␤-estradiol, on function, estrogen receptors/GPR30 expression, and kinase activation in vascular rings and cultured smooth muscle cells from arteries and veins of patients with coronary artery disease. Changes in vascular tone of internal mammary arteries and saphenous veins exposed to the steroid were recorded. 17␤-Estradiol caused concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
139
0
3

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 51 publications
(57 reference statements)
5
139
0
3
Order By: Relevance
“…35 Role of the novel ER G protein coupled receptor 30 (GPR30) in the cardiovascular system In addition to the two classical ER subtypes, ERa and ERb, a third membrane-bound and G-protein-coupled ER, GPR30, has been identified in human vascular endothelial cells (ECs) and smooth muscle cells. [36][37][38] Haas et al 37 reported that G-1, a selective stimulator of GPR30, acutely blocked vasoconstrictor-induced changes in intracellular calcium concentrations and vascular tone, resulting in lowering of blood pressure in normotensive rats. Similar vasodilator effects of GPR30 have been confirmed in other studies.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…35 Role of the novel ER G protein coupled receptor 30 (GPR30) in the cardiovascular system In addition to the two classical ER subtypes, ERa and ERb, a third membrane-bound and G-protein-coupled ER, GPR30, has been identified in human vascular endothelial cells (ECs) and smooth muscle cells. [36][37][38] Haas et al 37 reported that G-1, a selective stimulator of GPR30, acutely blocked vasoconstrictor-induced changes in intracellular calcium concentrations and vascular tone, resulting in lowering of blood pressure in normotensive rats. Similar vasodilator effects of GPR30 have been confirmed in other studies.…”
Section: Action Of Estrogen On the Cardiovascular Systemmentioning
confidence: 99%
“…From biodistribution studies, uptake of the radiotracer in the tumor was receptormediated based on the significantly lower uptake on coinjection with excess17b-estradiol. Care must be taken while performing receptor blocking experiments with high doses of 17b-estradiol as estrogen alters vascular physiology, blood flow and receptor expression levels (39). Consequently, when the blocking dose was injected 1 h before the injection of the radiotracer, we observed higher uptake in organs such as liver and lungs.…”
Section: Discussionmentioning
confidence: 82%
“…GPR30, has been detected in many tissues, including the uterus [22]. GPR30 expression was discovered in the vascular smooth muscle cells of patients with atherosclerosis [23]. Subsequently, it was found that GPR30 expression mediated the proliferation of ovarian [24], endometrial [10], breast [13], and sperm cell [25] tumors.…”
Section: Discussionmentioning
confidence: 99%